PLURALISME BERAGAMA PADA MASYARAKAT DESA TEGALAN KEDIRI - Tohari, Maula Safira Putri; Firdaus, Erina Dita; Hermansyah, Ervan Dwi; Putri, Alvia Nurystikha (Institut Agama Islam Ngawi, 2024)
Abstract: This research is motivated by the author's curiosity related to the form of religious harmony that exists in Tegalan Kediri Village as a Kediri area that has various religious adherents. The purpose of this research is to find out how the relationship between the Tegalan community in the midst of diversity. In addition, it also aims to find out what kind of tolerance model that exists there and how, as well as the form of application of interfaith dialogue through the interfaith dialogue forum that exists in the daily life of the Tegalan Kediri community. The results showed that the existence of interfaith activities was able to create arelationship between the Tegalan Kediri community to be peaceful, serene and far from conflict. Because the values of tolerance and Unity in Diversity are used as the basis for the Tegalan village community to coexist in diversity. This research was conducted using a qualitative method, in which the author has endeavoured to make observations of the destination and interviewed and did not forget to refer to articles that were able to become a reference source allowance. This research has also fully collected facts and data in accordance with observations and interviews with sources. Thus, this research is a descriptive qualitative research, so that all understandings, explanations, and findings are described or explained in the form of sentence descriptions as a result of critical and argumentative interpretations based on research data. Keywords: Practice, Pluralism, Religion